Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1097/01.mib.0000435849.17263.c5
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of an Amino Acid Mixture on Colonic Mucosal Healing in Rats

Abstract: Amino acid supplementation ameliorates colonic MH but not mucosal inflammatory status. Our data sustain the use of adjuvant dietary intervention on initiated intestinal MH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…1–6 weeks) [2]. Glutamate is known to be a chemotaxis-inducing factor for human neutrophils, and glutamate has demonstrated beneficial effects on both mucosal and epidermal wound healing [10, 14, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…1–6 weeks) [2]. Glutamate is known to be a chemotaxis-inducing factor for human neutrophils, and glutamate has demonstrated beneficial effects on both mucosal and epidermal wound healing [10, 14, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…Another example is the tryptophan metabolite kynurenate, which exerts antiinflammatory properties by inhibiting xanthine oxidase, resulting in decreased production of ROS during hypoxic stress (76). Likewise, glutamate, methionine, and threonine appear to improve colonic mucosal regeneration after insult (77). These examples provide insight into the integrated responses necessary for homeostatic regulation of tissue barrier function.…”
Section: Molecular Aspects Of Barrier Regulation In the Mucosamentioning
confidence: 99%
“…Another study performed in the same model has shown that the combination of threonine, methionine and glutamate supplementation ameliorates colonic MH but not inflammatory status [99]. Although the mechanisms of action by which the three AA accelerate the colonic MH remain unclear, it can be presumed, as already discussed above, that these AA may serve as building blocks for macromolecule synthesis in the wounded mucosal area, as energy substrates for anabolic pathways, and as precursors for bioactive metabolites [100].…”
Section: Potential Role Of Dietary Protein Intake and Amino Acid Smentioning
confidence: 99%
“…In animal studies, colitis has been shown to be associated with a marked increase in the protein fractional synthesis rate in the colon [99,119,120,121]. In addition, in a mice model of colitis, an HP intake (whole milk protein), although increasing the mortality of animals when compared to an isoenergetic NP diet, displayed beneficial effects on the surviving animals during the colitis remission phase [45].…”
Section: Potential Role Of Dietary Protein Intake and Amino Acid Smentioning
confidence: 99%